ANALYSIS OF MARKET REACTION TO THE PUBLICATION OF FINANCIAL REPORTS OF PHARMACEUTICAL COMPANIES BEFORE AND DURING THE COVID-19 PANDEMIC - I Kadek Arka Marthayana; I Made Pande Dwiana Putra (INTERNATIONAL JOURNAL OF ECONOMIC LITERATURE, 2024)
The Covid-19 pandemic has had an impact on share prices on the capital market. This is different from pharmaceutical companies whose share prices increased during the Covid-19 pandemic. This research aims to determine the market reaction as seen from the difference in average abnormal returns before and after the publication of pharmaceutical company financial reports before and during the Covid-19 pandemic. The grand theory of this research is the Efficient Market Hypothesis. The research was conducted using an event study for 15 days (t-7 to t+7) of the publication of financial reports. The population of this study used 10 pharmaceutical companies registered on the IDX for the period 2019 and 2021. The sample for this study was 40 samples each year. The hypothesis test for this research is the one sample t-test and the Wilcoxon signed rank test. The results of the hypothesis test show that before Covid-19, there was no difference in the average abnormal return before and after the publication of financial reports. However, during the Covid-19 pandemic, there was a significant difference in average abnormal returns before and after the publication of financial reports. This shows a comparison of the difference in average abnormal returns before and after the publication of pharmaceutical company financial reports before and during the Covid-19 pandemic. This indicates that financial reports published during the Covid-19 pandemic influenced investors in making investment decisions.